Citizenship and identity - Isin, Engin F. (Engin Fahri) 1959-; Wood, Patricia K. (London SAGE, 1999)
Through a detailed introductory discussion of the relation between the civil and the political, and between recognition and representation, this book provides a comprehensive vocabulary for understanding citizenship. It uses the work of T H Marshall to frame the critical interrogation of how ethnic, technological, ecological, cosmopolitan, sexual and cultural rights relate to citizenship.
Keywords: Citizenship; Identity (Psychology); Group identity